2022
DOI: 10.1021/acsearthspacechem.2c00047
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Brown Carbon Aerosols during Atmospheric Long-Range Transport in the South Asian Outflow and Himalayan Cryosphere

Abstract: The Himalayas sustain the water sources for ∼2 billion people in South and East Asia. The Himalayan cryosphere is particularly sensitive to climate change as a result of long-range transport of anthropogenic emissions from the Indo-Gangetic Plain. Atmospheric warming as a result of light-absorbing aerosols, i.e., black carbon (BC) and brown carbon (BrC), is responsible for accelerated loss of glaciers in the region. The BrC lifetime in the atmosphere over the Himalayan cryosphere has never been studied before,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 88 publications
0
7
1
Order By: Relevance
“…can transform the chemical composition and optical properties of BrC aerosols following their emissions or formation. 7,9,[31][32][33] Previous laboratory studies on aqueous-phase photochemical oxidation of secondary BrC showed rapid loss of chromophores also referred to as photobleaching. 29,30 However, photo-enhancement preceded photobleaching for biomass burning primary BrC aerosols.…”
Section: Introductionmentioning
confidence: 99%
“…can transform the chemical composition and optical properties of BrC aerosols following their emissions or formation. 7,9,[31][32][33] Previous laboratory studies on aqueous-phase photochemical oxidation of secondary BrC showed rapid loss of chromophores also referred to as photobleaching. 29,30 However, photo-enhancement preceded photobleaching for biomass burning primary BrC aerosols.…”
Section: Introductionmentioning
confidence: 99%
“…Through reactions occurring inside particles, as well as interactions with gas-phase molecules, its composition and effects are additionally modified. 14–19…”
Section: Introductionmentioning
confidence: 99%
“…Through reactions occurring inside particles, as well as interactions with gas-phase molecules, its composition and effects are additionally modified. [14][15][16][17][18][19] Recent studies have demonstrated that photochemical processing of biomass burn plumes in the atmosphere leads to the formation of anhydrides through aromatic oxidation and furan chemistry. [20][21][22][23][24][25] Specifically, maleic and phthalic anhydride represent two significant primary emissions from the combustion of biomass.…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric WSOC originated from primary emissions, including biomass burning, coal burning, and other primary sources (Park and Yu, 2016;Li et al, 2018;Tang et al, 2020); as well as the secondary formations, such as the aqueous-phase reaction from anthropogenic or biogenic emission (Gilardoni et al, 2016;Lamkaddam et al, 2021;Updyke et al, 2012;Yu et al, 2021). Light-absorbing WSOC is an important component of brown carbon (BrC) and has a strong wavelength-dependent absorption that peaks in the ultraviolet (UV) spectral region and declines through the visible spectral region (Choudhary et al, 2022;Hecobian et al, 2010;Laskin et al, 2015;Sullivan et al, 2022). This fraction can contribute significantly to the global radiation balance and affects the photochemistry of the atmosphere (Feng et al, 2013;Kirchstetter and Thatcher, 2012).…”
Section: Introductionmentioning
confidence: 99%